Strengthening the Pillars of Sustainable Tourism Through Language, Culture and Health Education for the Nation's Next Generation Belantih Village, Kintamani Bangli - PUTRA, Gede Sanjaya Adi; SARI, Ni Luh Putu Eka Kartika; SELAMET, I Ketut (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
Belantih Village in Kintamani, Bali, offers beautiful natural scenery and coffee and orange plantation agrotourism that supports tourism. The village has great potential but needs more English language skills, which hinders interaction with tourists. KKN in this village, which focuses on teaching English, dance, and healthy living behaviors, is essential to improve competitiveness in the tourism sector, preserve Balinese culture, and improve quality of life. The community service program in Belantih Village, Kintamani, integrates English language education, arts, and healthy living practices to empower elementary students. The program aims to enhance students' language proficiency, artistic expression, and hygiene awareness through structured instruction and hands-on activities, ultimately contributing to sustainable tourism and community well-being. Evaluation will include pre- and post-assessments, feedback, and a final showcase to measure and celebrate the program's impact on the student's personal development and community contribution. This program is expected to have a long-term impact on community welfare and readiness to face future health challenges. Warmadewa KKN students supported sustainable tourism in Belantih Village by teaching elementary students English, traditional dance, and healthy living.